Pemanfaatan Data Pengamatan Pilot Ballon untuk Analisis Kondisi Atmosfer sebelum Terjadinya Hujan Lebat di Wilayah Samarinda (Studi Kasus 2015 – 2022) - Alhadid, Bai'at (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2024)
Heavy rain is a type of extreme weather that is generally caused by Cumulonimbus clouds. Heavy rains occur quite frequently in Indonesia, especially in Samarinda during 2015 – 2022. There has been quite a lot of research on heavy rain. Another approach that can be used for research on heavy rain is upper air observation data. From that data, air movement and atmospheric lability can be determined. One of the instruments used for upper air observations is the Pilot Balloon (Pibal). In addition, not enough utilization of Pibal observation data has been carried out. Therefore, this research will utilize Pibal observation data to analyze atmospheric conditions before heavy rains in Samarinda during 2015 – 2022. Pibal observation data is processed using RAOB 5.7, so that air movement and atmospheric lability can be determined (850 mb wind speed, Bulk Richardson Number (BRN) Shear, and Storm Relative Helicity (SRH)). The results of this study indicate that before heavy rain occurs, air movement from the surface layer to 3 km generally moves clockwise, which indicates convective activity that can support cloud formation and rain. However, the atmosphereic lability values observed before the occurrence of heavy rains are generally quite low. Only one incident (K10) showed that the atmospheric lability was high that can increase that convective activity and the formation of Cumulonimbus clouds. On K10 there is an increase windspeed on the 850 mb which reached 32 knots, high BRN Shear and SRH values, reaching 26 m2/ s2 dan 226 m2/ s2.